The relationship between leadership styles and leadership effectiveness in Malaysian Government Linked Companies (GLCS) / Sharifah Rahama Amirul - Amirul, Sharifah Rahama (2014)
The aspiration of government linked companies (GLCs) to be global and domestic champion in 2015 urged the need of effective leadership in transforming GLCs to attain breakthrough performance as well as to maintain industrial harmony. Hence, it is essential to understand how leaders play important roles through examine the relationship between leadership styles and leadership effectiveness in Malaysian GLCs context. Another, as a developing country, diversity in Malaysia has increased, thus including demographic factors (gender, age, working experiences) in this study is also vital to understand what constitutes effective leaders. The study encompassed three styles of leaders as proposed by the full range of leadership (FRL) theory and the sample was strictly drawn from the employees of G20 (selection of largest GLCs participated in GLCs transformation programme) through multistage sampling method. As results, the study found that transformational leadership style was the most effective followed by transactional leadership style. As an integrative approached of FRL theory, the injections of transformational character into transactional leadership style would makes GLCs leaders even more effective. Contrarily to passive/avoidant style, it was not significant to leadership effectiveness. Based on study’s findings, GLCs leaders were most likely to practice transactional leadership style, thus GLCs must take initiative to vaccinate more transformational leadership style on GLCs leaders. Another, the study has also found that working experience and leadership styles was significantly different but no significant differences found between gender and age in the linear combination of leadership styles. The study has brought awareness to GLCs leaders to play their important roles by practicing the right style to be more effective as well as sensitive to the differences of employees’ working experiences.